Chloe in the know - Caseley, Judith (New York : Greenwillow Books, 1993)
Chloe's close and caring family supports her when she begins to feel the strain of being the oldest child. (Gr. 2-4)
Keywords: Family life -- Fiction; Brothers and sisters -- Fiction